Parents knowledge on premature baby care in Hospital University Science Malaysia (HUSM). - Desa, Fatimah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
Premature babies are those born before 37 weeks of gestation. Parents of premature babies need to have basic knowledge in caring for these babies as their life are at high risk . This study is to study the knowledge level in premature baby care in parents whose children are receiving treatment at HUSM. This study is done to study the knowledge level and socioeconomic factor influencing parents in care of premature baby at HUSM. This is a cross-sectional study toward 60 respondents who have premature babies and receiving treatment at HUSM. This study using questionnaire and the data was analyzed using 'Statistical Package For Social Science' (SPSS) version 12.0. From this study, the knowledge of respondents in the care of the premature baby was acceptable. Overall, the knowledge of respondents was 90% regarding feeding, 81.1% immunization, 62% bonding, 61% regarding birth premature babies, 56.5% healthcare, and 56% physical development. The result showed that the majority respondents have knowledge due to previous experience of caring for these babies during hospitalization and also from nurses and doctors treating the baby. Generally, most premature baby grow normally and their development is also normal but they need special care while they are growing. Nurses, have to be prepared in providing information and knowledge to parents who have premature babies so that they can apply the knowledge in caring for their premature baby. When the parents have enough knowledge regarding care of premature baby the caring process can be done in a proper and satisfactory manner.